Evaluasi Kinerja Keuangan UMKM Pasca-Pandemi: Studi Kasus pada Sektor Kuliner di Kota Bandung - Melati Puspita Hakim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The COVID-19 pandemic disrupted the operational and financial stability of culinary SMEs in Bandung, Indonesia. This qualitative study analyzes post-pandemic recovery strategies among 15 culinary SMEs through in-depth interviews, participatory observation, and document analysis (2021-2023). Findings identify three recovery phases: (1) survival (2021) via online sales adaptation and strict health protocols, (2) stabilization (2022) through localized supply chain optimization, and (3) limited expansion (2023) marked by Sundanese local wisdom-based ready-to-cook product diversification. Key resilience strategies involved collaborative resource-sharing and collective marketing within SME communities. While 73% of respondents reported a 20-40% revenue increase by 2023, micro-SMEs (<5 employees) faced structural challenges, particularly reliance on high-interest informal loans (15-20%/month), absorbing 30-45% of net profits. The study underscores the synergy of local wisdom and community collaboration as pillars of inclusive recovery. Policy recommendations include: (1) community-based technical mentoring for SME digitization, (2) long-term microfinancing schemes (<5% interest) via public-private partnerships, and (3) integration of Sundanese cultural elements into unified digital marketing platforms. This research contributes a sustainable recovery framework for post-crisis SMEs in emerging economies, blending socio-cultural and institutional dimensions.